Strengthening Financial Control in Public Procurement as a Way of Counteracting Economic Crimes - Moroz, Yuliia; Konopelskyi, Viktor; Zholnovych, Ihor; Skrylnik, Andrey; Danileviča, Alina (Theoretical and Practical Research in Economic Fields, 2026)
Purpose: The relevance of the study is determined by the need to increase the effectiveness of countering economic crimes through the optimization of control mechanisms in the field of public procurement based on indicator-metric monitoring and institutional stratification. The aim of the research is the formalization and verification of the framework for financial control of procurement, considering anti-corruption metrics, digital monitoring, and algorithmic auditing under regulatory variability. Methodology: The study is based on the application of the following methods: strategic stratification, econometric modelling, decomposition analysis, synthesis modelling, comparative analysis Findings: The study verified procurement frameworks through stratification, econometric modelling, and decomposition analysis. It was found that KONEPS has the best baseline performance (Cost Savings – 75%, LCR – 0.002, ROI – 12.5) but is limited by cybernetic inertia. The developed framework outperforms the specified metrics: Cost Savings – 82.7%, ROI – 14.2, LCR – 0.0015, CPI – –8.6, MCR – 0.007. The results demonstrate increased control resilience, institutional coherence, and regulatory adaptability. Originality: The academic novelty of the research lies in the synthesis modelling of a procurement framework optimized by financial monitoring for multi-level control and traceability. The Price Efficiency Index and Monitoring Cost Ratio metrics were introduced for the first time, while LCR and Control ROI were modernized for metric-based performance assessment. Prospects for further research may be the development of a pilot experiment to implement an optimized framework in a limited administrative environment to assess its institutional integration.